Low-field MRI at high magnetic field instability and inhomogeneity conditions - Rodriguez, Gonzalo G.; Schürrer, Clemar A.; Anoardo, Esteban (Frontiers in Physics, 2023)
Understanding the effects of the magnetic field time instabilities in magnetic resonance imaging (MRI) is fundamental for the success of portable and low-cost MRI hardware based on electromagnets. In this work we propose a magnetic field model that considers the field instability in addition to the inhomogeneity. We have successfully validated the model on signals acquired with a commercial NMR instrument. It was used to simulate the image defects due to different types of instability for both the spin-echo and the gradient-echo sequences. We have considered both random field fluctuations, and an instability having a dominant harmonic component. Strategies are suggested to minimize the artifacts generated by these instabilities. Images were acquired using a home-made MRI relaxometer to show the consistency of the analysis.The development of low field MRI instruments (< 0.2 T) is growing drastically [1-3] motivated by the possibility of cost reductions [4,5], portability [6-10], and contrast-enhancement [11]. However, critical points to consider are the lower signal to noise ratio (SNR) [12], magnetic field homogeneity [9], and magnetic field stability [13]. These limitations may strongly affect the image quality by introducing biasing and artifacts. Therefore, the success of low field scanners strongly depends on our ability to minimize or compensate these undesired effects.In MRI experiments the SNR degrades with the magnetic flux density (B 0 ) as B 0x , with an exponent x ranging from 1.65 to 1.75 [12,14]. In consequence, the SNR working conditions for low-field MRI can be much poorer that those usually available at high-field MRI. However, the SNR can be improved by different means, from a simple signal averaging to different hardware and computational contraptions. Some explored hardware solutions include, among other, hyperpolarization schemes [11], magnetic field-cycling technology [3,13,15], single or multiple receiver channels using superconducting quantum interference devices (SQUID) [16][17][18] and coupling to external resonators or magnetic lenses for signal enhancement [19][20][21]. Specially designed pulse sequences are also considered [22,23], while image pos-processing can be used to artificially enhance the image SNR [24,25].